ANALISIS HUKUM ATAS PERJANJIAN KERJA SAMA TRANSPORTASI ANGKUTAN BBM MODA MOBIL TANGKI ANTARA PT. PERTAMINA (PERSERO) DENGAN PT. MITRA WAHYU PRAKASA DI TBBM DUMAI DAN TBBM SIAK - HEMA YOSI FIDIANA (PREMISE LAW JURNAL, 2016)
DOSEN PEMBIMBING:1. Muhd Yamin 2. Syafruddin Kalo 3. T. Keizerina Devi A The role of transportation mode of tank truck in carrying BBM (fuel oil) to industrial location is highly needed for the sake of consumers and equal distribution. In Dumai and Siak which are very wide, PT Pertamina (Persero) needs several agents in distributing fuel oil in order to expedite fuel oil delivery. Since PT MitraWahyuPrakasa had won the tender for collaborating with PT Pertamina (Persero), the collaboration between the two parties was established. In order to find out the content of the contract, it was necessary to analyze the cooperative agreement between the two parties. The conclusion of the research was that the contract on BBM mode transportation of tank trucks was not made in authentic deed. Here, PT Pertamina (Persero) wanted only one contract for many transportation companies in many areas quickly in order to save money, time, and energy. Therefore, the contract between the two parties was made by PT Pertamina (Persero) Region 1, Medan in a standard contract. The problem was that there was no balance between the right and the obligation since PT Pertamina (Persero) was more dominant than PT MitraWahyuPrakasa. The legal consequence was that when one of the parties breached of contract (default), there would the sanctions of warning, suspension, indemnity, termination of cooperative relationship from PT Pertamina (Persero), and criminal sanction. The consequence of force majeure was that here would be no responsibility for the failure and/or the lateness in carrying out the duties. Keywords:   BBM Mode Transportation of Tank Truck, Standard Contract, Authentic